Local integrals of motion in the two-site Anderson-Hubbard model. (1st September 2017) - Wortis, R; Kennett, Malcolm P
Abstract: It has been proposed that the states of fully many-body localized systems can be described in terms of conserved local pseudospins. Due to the multitude of ways to define these, the explicit identification of the optimally local pseudospins in specific systems is non-trivial. Given continuing intense interest in the role of disorder in strongly correlated systems, we consider the disordered Hubbard model. By studying a small system we provide concrete examples of the form of local integrals of motion in the Anderson-Hubbard model. Moreover, we are able not only to identify the most local choice but also to explore the nature of the distribution of possible choices. We track the evolution of the optimally localized pseudospins as hopping and interactions are varied to move the system away from the trivially localized atomic limit.